Evaluasi Heuristic Desain Antar Muka (Interface) Portal Mahasiswa (Studi Kasus Portal Mahasiswa Universitas X) - Caesaron, Dino (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2015)
This study aimed to evaluate the interface design of student portal in University X using human factors and ergonomics interpretation approach, to increase usability and usefulness of the system. Heuristic evaluation by Molich and Nielsen was used as methodology. The result shows in general that interface design, ease of use (usability) of student portal in University X has been pretty good based on evaluation, but there are some things that need to be improved, especially in the characteristics of usability